2001
DOI: 10.1161/hc37t1.094855
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Tissue Doppler Wall Motion Monitoring After Heart Transplantation for Replacement of Invasive Routine Screenings by Optimally Timed Cardiac Biopsies and Catheterizations

Abstract: Background-Invasive screenings at predefined time intervals for acute rejection and transplant coronary artery disease (TxCAD) are standard procedures. However, cardiac biopsies and catheterizations are distressing and risky for the patients and are also costly. We assessed the reliability of pulsed-wave tissue Doppler imaging (PW-TDI) for the timing of invasive examinations in heart recipients in an attempt to avoid unnecessary endomyocardial biopsies (EMBs) and catheterizations. Methods and Results-PW-TDI ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(40 citation statements)
references
References 15 publications
2
38
0
Order By: Relevance
“…It has been widely accepted that tissue Doppler echocardiography (TDE) is useful in analyzing subclinical ventricular functions in some cases such as valve regurgitation, anthracycline cardio toxicity, earlier phases of cardiomyopathies and heart transplant rejection [5][6][7][8] . However, the number of studies on TDE's role in analyzing cardiac functions, and the spectrum and frequency of cardiac involvement in children with CD is limited 9,10 .…”
mentioning
confidence: 99%
“…It has been widely accepted that tissue Doppler echocardiography (TDE) is useful in analyzing subclinical ventricular functions in some cases such as valve regurgitation, anthracycline cardio toxicity, earlier phases of cardiomyopathies and heart transplant rejection [5][6][7][8] . However, the number of studies on TDE's role in analyzing cardiac functions, and the spectrum and frequency of cardiac involvement in children with CD is limited 9,10 .…”
mentioning
confidence: 99%
“…8 It has been observed that early diastolic peak velocity and isovolumetric relaxation time in the basal portion of the left ventricle lateral wall measured by pulse wave tissue Doppler had a high sensitivity in diagnosing rejection, especially those higher than grade II. 9 Stengel and associates 10 reported that high late diastolic mitral annulus velocity was effective in diagnosis of grade III and higher severe rejections. Therefore, it was observed that tissue Doppler was effective in demonstrating diastolic dysfunction in severe rejection.…”
Section: Discussionmentioning
confidence: 99%
“…TDI-derived indices have been shown to be useful in predicting subtle cardiac injuries when conventional indices of LV function are still normal. In a study conducted on nearly 400 biopsies using PW-TDI, significant allograft rejection (≥ grade 2) was shown to be associated with a significantly reduced peak early diastolic velocity (Em,) and a significantly prolonged early diastolic time (TEm) of the basal LV inferolateral wall (37). Three smaller studies have also demonstrated that Em significantly reduced in allograft rejection (23,38,39).…”
Section: Discussionmentioning
confidence: 99%